Gray hat hacking the ethical hacker's handbook - Harper, Allen (McGraw-Hill, 2011)
An introduction to the art of ethical hacking for professionals and security analysts addresses a range of moral and legal issues regarding hacking, offers detailed instructions, countermeasures, and moral disclosure procedures.